Implementation of Therapeutic Communication at Dr. Pirngadi Hospital - Kholil, Syukur; Lubis, Lahmuddin; Ritonga, Syafruddin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study aims to study intensively about therapeutic communication at General Regional Hospital of Dr. Pirngadi Medan. This research is a field research with a qualitative approach. In this study researchers used data collection obtained by conducting research directly in the field. The result shows that implementation of Islamic Communication in therapeutic communication carried out by medical personnel at General Regional Hospital of Dr. Pirngadi Medan applies therapeutic communication in Islamic communication, such as greeting when entering a room, greeting each patient before checking and asking about the development of they health. This is a form of communication that must be carried out by every medical personnel. The model of implementation of Islamic communication in therapeutic communication for healing patients at General Regional Hospital of Dr. Pirngadi Medan is Interpersonal Communication which is considered the most effective because of its dialogical nature in the form of conversation.